Functional performance, nutritional status and level of physical activity of elderly (Bioscience Journal, 2022)
The elderly is a risk group for changes in health conditions and as well as in functional performance related to the decline in grip strength and reduced walking speed, which can compromise the performance of activities of daily living. Based on this, the objective was to analyze the factors associated with functional performance in the elderly. For that, a cross-sectional study was developed involving a group of 179 elderly people who received medical care at an outpatient clinic of the public health network. Muscle strength and gait speed were measured. Nutritional status was determined by Body Mass Index (BMI), calf circumference (CC), waist circumference (WC) and waist-to-hip ratio (WHR). Level of physical activity was measured by the adapted version of the Minnesota Leisure Activities Questionnaire. Low muscle strength was found in 20.7% of the elderly and slow gait in 20.1%. Increased risk of cardiovascular disease was found in 40.8% considering WC, and 35.2% by WHR. Most of the elderly had low weight and no loss of muscle mass. Loss of muscle strength was associated with sex and CC and gait speed were associated with sex, age, and presence of a partner (p < 0.05). The chance of loss of muscle strength and lower gait speed was higher in elderly women. Loss of muscle mass due to CC was associated with the chance of loss of strength, and the chance of reduced walking speed was greater among the elderly individuals aged 75 years and over.